1988
DOI: 10.1111/j.1346-8138.1988.tb03690.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Dermatomyositis and Hashimoto's Thyroiditis

Abstract: We report a 59-year-old female patient with dermatomyositis associated with Hashimoto's thyroiditis. It is generally agreed that overlap of autoimmune diseases occurs during their course. The relationship between dermatomyositis and Hashimoto's thyroiditis is discussed in terms of autoimmune diseases, and several similar cases in the literature are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A total of 11 patients 8–12 who met our criteria were included. Two patients were excluded because of insufficient data, 13,14 and one case with juvenile DM and subclinical hypothyroidism was also excluded 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 11 patients 8–12 who met our criteria were included. Two patients were excluded because of insufficient data, 13,14 and one case with juvenile DM and subclinical hypothyroidism was also excluded 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been generally accepted that autoimmune thyroiditis (AIT), an organ‐specific autoimmune disease, may often become related to systemic autoimmune diseases, for instance, SLE, PSS and rheumatoid arthritis (RA) 5–7 . However, the reports on the association of DM with AIT are very few, to our knowledge, the association between them has been reported in six cases 8–12 . From these limited evidences, a cross‐linkage of autoimmune disease or a common genetic basis, may be present in these patients, although we can not exclude the possibility that the relationship represents a random finding.…”
Section: Introductionmentioning
confidence: 87%
“…Autoimmune CDI has rarely been described in the literature and is usually induced by the global damage of the hypothalamic regions by autoantibodies to the arginine vasopressin-secreting cells (AVPcs) (3,9). Pivonello et al showed the likelihood of AVPc autoantibodies (Abs) positivity of 99% in their study, when all of the following were present: the age at disease onset of <30 years, history of autoimmune disease, and the presence of pituitary stalk thickening, and an 80-82% likelihood when two of the above parameters were present (10). This test was not performed in our case because the test is still not routinely performed in the laboratory, but is primarily done for research purposes only.…”
Section: Discussionmentioning
confidence: 99%
“…DI was shown to be linked with other autoimmune connective tissue disorders such as systemic lupus erythematosus, Sjögren's syndrome, and systemic sclerosis (13). On the other hand, DM is also known to overlap with autoimmune thyroiditis (10,14), type I diabetes mellitus, celiac disease, myasthenia Gravis (15,16,17), and also together with both T1DM and thyroiditis (18).…”
Section: Discussionmentioning
confidence: 99%
“…JDM is classified as a separate disease entity because of the presence of generalised vasculitis [5]. Mild muscle weakness and elevated CK are well known to be accompanied by hypothyroidism [2], however, there have been only a few case reports, mostly adults, of the combination of dermatomyositis and auto-immune hypothyroidism [1,2,3,6]. In a Japanese national survey of JDM between 1984 and 1994, only one case of chronic thyroiditis was associated with JDM [4].…”
mentioning
confidence: 99%